Reflections on Soft Skills and their interfaces with BNCC in the context of Remote (Research, Society and Development, 2020)
Today we live in an increasingly connected world, where digital information and communication technologies, also known as TDICs, have impacted and changed our ways of communicating, of relating, in addition to the way we work and learn. The COVID-19 pandemic accelerated the transformation of education and directly impacted the teaching-learning process, and brought irreversible effects on education. Teaching will never be what it was before. We break free from the classroom walls and discover a world of opportunities and challenges. This study seeks to broaden the discussion about the reflection of Soft Skills and their interfaces with BNCC in the context of emergency Remote Education, with particular emphasis on non-technical skills.